1994
DOI: 10.1172/jci117463
|View full text |Cite
|
Sign up to set email alerts
|

M protein and protein F act as important determinants of cell-specific tropism of Streptococcus pyogenes in skin tissue.

Abstract: The pathogenic gram-positive bacterium Streptococcus pyogenes (group A streptococcus) causes numerous diseases of cutaneous tissue, each of which is initiated after the interaction of the bacterium with the cells of the epidermis. In this study, we show that different surface proteins of S. pyogenes play important roles in determining the cell-specific tropism of the bacterium in skin. Using streptococcal strains with defined mutations in the genes which encode surface proteins in combination with primary cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 48 publications
(34 reference statements)
6
133
2
Order By: Relevance
“…pyogenes may utilize different adhesins for attachment and colonization of different tissues and for invasion. For instance, M protein may mediate adherence to keratinocytes in the epidermis, whereas SfbI may be necessary for adherence of group A streptococcus to pharyngeal cells and Langerhans' cells, a component of the basal layer of the epidermis [25]. Different repertoires of adhesins and their regulators, and the interactions of the adhesins with each other may determine tissue tropism and pathogenicity of S. pyogenes.…”
Section: Resultsmentioning
confidence: 99%
“…pyogenes may utilize different adhesins for attachment and colonization of different tissues and for invasion. For instance, M protein may mediate adherence to keratinocytes in the epidermis, whereas SfbI may be necessary for adherence of group A streptococcus to pharyngeal cells and Langerhans' cells, a component of the basal layer of the epidermis [25]. Different repertoires of adhesins and their regulators, and the interactions of the adhesins with each other may determine tissue tropism and pathogenicity of S. pyogenes.…”
Section: Resultsmentioning
confidence: 99%
“…Increased susceptibility to phagocytic killing in vitro may predict rapid phagocytic clearance of the M protein-deficient GAS strain from the throat in vivo. However, it is also possible that M protein-deficient GAS are rapidly cleared from the pharynx because they are defective in attachment to pharyngeal epithelia (Hasty et al, 1992;Okada et al, 1994;Schrager et al, 1998). The requirement for M protein in primate pharyngeal colonization was not predicted by previous studies in mice which demonstrated that M protein-deficient GAS were comparable with wildtype GAS in their ability to colonize the throat, but is consistent with the role of M protein as a critical virulence factor for the organism in in vitro phagocytic assays, murine intraperitoneal infection and murine invasive infection (Lancefield, 1962;Husmann et al, 1997;Moses et al, 1997;Ashbaugh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For a number of strains, host cell entry requires bacterial binding of serum Fn. In these cases, bacterial-bound Fn appears to function as a bridging molecule, promoting bacterial interaction with host Fn receptors (13,16,17,19).…”
Section: T He Gram-positive Bacterial Pathogen Streptococcus Pyogenesmentioning
confidence: 99%